Скарб кола Мартинівки з Правих Солонців Херсонської області - Ганощенко, В.В.; Володарець-Урбанович, Я.В. (Археологія і давня історія України, 2019)
Статтю присвячено знахідці прикрас доби раннього середньовіччя у степовій смузі України, що
були виявлені 2017 р. поблизу Правих Солонців Херсонської обл. Визначено їхнє місце і дату серед старожитностей цього часу, висунено можливі варіанти пояснення появи такого комплексу на далекій периферії основного регіону поширення таких речей. Article presents jewelry findings from Pravi Solontsi
in the Lower Dnieper. The assemblage belongs to the
circle of Dnieper early medieval hoards of first chronological
group by O. A. Shcheglova or Martynivka type. The complex comprises 20 whole and fragmented
metal items and 1 glass bead. All jewelry is represented by elements of women’s attire: details of collar (chain
with link of «snake head», tubular beads Volodarets-Urbanovich / type 1, trapezoidal pendants ornamented with two / three punches circles in mid and blue bead) and bracelets (Rodinkova / type 5, subtype 3 and 2, Rodinkova / type 2, subtype of ornamented).